Optimizing Project Administrative Workflow with Formstack, Sharepoint, and Vanderbilt CORES Software - Vinson, Paige (Association of Biomolecular Resource Facilities, 2013)
Tracking administrative workflow for Core projects is a difficult task. Cores are increasingly required to provide metrics demonstrating productivity, scope of projects, and success rates, yet scientific staff members do not have sufficient access or bandwidth to produce this type of broad spectrum data easily. In an effort to reduce redundancy, automate recurrent tasks and minimize staff labor, the Vanderbilt High Throughput Screening (HTS) Facility has combined readily available web-based software with institutional CORE software. The HTS Facility is striving toward a goal of having common sets of metrics available, as needed, to communicate the institutional impact of the Core to senior leadership and funding agencies. These administrative workflow improvements also increase effective and efficient communication in daily project administration and minimized required labor from scientific staff.